Microbial Community Structure and Methane Cycling Potential along a Thermokarst Pond-Peatland Continuum - Adrien Vigneron; Perrine Cruaud; Najat Bhiry; Connie Lovejoy; Warwick F. Vincent (Microorganisms, 2019)
The thawing of ice-rich permafrost soils in northern peatlands leads to the formation of thermokarst ponds, surrounded by organic-rich soils. These aquatic ecosystems are sites of intense microbial activity, and CO2 and CH4 emissions. Many of the pond systems in northern landscapes and their surrounding peatlands are hydrologically contiguous, but little is known about the microbial connectivity of concentric habitats around the thermokarst ponds, or the effects of peat accumulation and infilling on the microbial communities. Here we investigated microbial community structure and abundance in a thermokarst pond-peatland system in subarctic Canada. Several lineages were ubiquitous, supporting a prokaryotic continuum from the thermokarst pond to surrounding peatlands. However, the microbial community structure shifted from typical aerobic freshwater microorganisms (Betaproteobacteria and Alphaproteobacteria) in the pond towards acidophilic and anaerobic lineages (Acidobacteria and Choroflexi) in the connected peatland waters, likely selected by the acidification of the water by Sphagnum mosses. Marked changes in abundance and community composition of methane cycling microorganisms were detected along the thermokarst pond-peatland transects, suggesting fine tuning of C-1 carbon cycling within a highly connected system, and warranting the need for higher spatial resolution across the thermokarst landscape to accurately predict net greenhouse gas emissions from northern peatlands.